Greenhouse emissions and productivity growth - Pantelis Kalaitzidakis; Theofanis P. Mamuneas; Thanasēs Stengos (Journal of Risk and Financial Management, 2018)
In this paper, we examine the effect of emissions, as measured by carbon dioxide (CO 2), on economic growth among a set of OECD countries during the period 1981-1998. We examine the relationship between total factor productivity (TFP) growth and emissions using a semiparametric smooth coefficient model that allow us to directly estimate the output elasticity of emissions. The results indicate that there exists a monotonically-increasing relationship between emissions and TFP growth. The output elasticity of CO 2 emissions is small with an average sample value of 0.07. In addition, we find an average contribution of CO 2 emissions to productivity growth of about 0.063 percent for the period 1981-1998.
Keywords: 330; TFP growth; emissions; materials balance condition; semiparametric estimation